Resposta espécie-específica à perturbação humana na seleção de local de nidificação de dois sabiás urbanos - Ferreira, Mariane Paduin (Universidade Federal de São Carlos, 2022)
Nest-site selection is an important decision for birds, relating to offspring survival and parental investiment. Considering the trade off of different strategies and the quality of available spaces, this decision may change in response to environmental changes. In urban environments, human disturbance can affect birds’ reproduction in different ways, but there are still relatively few studies testing the role of human disturbance in nest-site choice. The goal of this study was to identify plasticity in nest-site selection for Pale-breasted Thrush (Turdus leucomelas, VIEILLOT, 1818) and for Creamy- bellied Thrush (Turdus amaurochalinus, CABANIS, 1850), in higher and lower human disturbance situations on an university campus in southeastern Brazil. Nests were located during five breeding seasons, three with higher (2017-2019) and two with lower human movement due to COVID-19 pandemic (2020 and 2021), the nests’ height in relation to the ground was analyzed and its distance to the nearest human passageway. Results showed the more intense people moviment, higher were the nest heights for T. amaurochalinus. For the distance between nests and human passageways, there was a significant difference between the species as well and the more intense people movement proved to have na influence only for T. leucomelas, which in those years built its nests further away from the passageways. For both species, human disturbance may influence nest-site selection in a species-specific behavioral response.
Species-specific response to human disturbance in the nesting site selection of two urban thrushes
Keywords: Ninhos; Plasticidade comportamental; Reprodução; Turdus; CIENCIAS BIOLOGICAS::ECOLOGIA